2012
DOI: 10.1002/ajp.22106
|View full text |Cite
|
Sign up to set email alerts
|

Development of Snake‐Directed Antipredator Behavior by Wild White‐faced Capuchin Monkeys: I. Snake‐Species Discrimination

Abstract: Young animals are known to direct alarm calls at a wider range of species than adults. Our field study examined age-related differences in the snake-directed antipredator behavior of infant, juvenile, and adult white-faced capuchin monkeys (Cebus capucinus) in terms of alarm calling, looking behavior, and aggressive behavior. In the first experiment, we exposed infant and juvenile white-faced capuchins to realistic-looking inflatable models of their two snake predators, the boa constrictior (Boa constrictor) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 29 publications
1
39
0
1
Order By: Relevance
“…Thus, snake scales alone (i.e., without curvilinear cues) were sufficient for detection. Further support for the role of scales in driving snake detection comes from research that has demonstrated that white-faced capuchin monkeys ( Cebus capucinus ) respond more strongly to snake models with scales than to white snake models without scales20. Here we examined whether humans are also highly responsive to partially exposed snakes and specifically to snake skin scales by employing EEG.…”
mentioning
confidence: 99%
“…Thus, snake scales alone (i.e., without curvilinear cues) were sufficient for detection. Further support for the role of scales in driving snake detection comes from research that has demonstrated that white-faced capuchin monkeys ( Cebus capucinus ) respond more strongly to snake models with scales than to white snake models without scales20. Here we examined whether humans are also highly responsive to partially exposed snakes and specifically to snake skin scales by employing EEG.…”
mentioning
confidence: 99%
“…Realistic-looking models of these predators engendered the same recognition of potential threats that characterized the actual threats (Coss & Ramakrishnan, 2000;Meno, Coss, & Perry, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…; Meno et al. ). Immature individuals acquire the appropriate response to the alarm calls by observing adults (Seyfarth & Cheney ; Mateo & Holmes ; Hollén & Manser ; Meno et al.…”
Section: Introductionmentioning
confidence: 98%